Investigating language learning strategies (LLS) employed by ESL undergraduates in enhancing speaking skills in Universiti Tunku Abdul Rahman - Goh, Kai Ling (2024)
This study investigated language learning strategies (LLS) employed by ESL undergraduates to enhance speaking skills. Around 30 participants from the four faculties of the Faculty of Business and Finance (FBF), Faculty of Arts and Social Science (FAS), Faculty of Science (FSc) and Faculty of Engineering and Green Technology (FEGT) who study at Universiti Tunku Abdul Rahman (UTAR) were involved in this study. This study adopted a quantitative design that employed the Oxford SILL questionnaire (1990). The result indicated that cognitive and compensation are the most preferred language learning strategies among the participants of the four faculties regardless of gender. There is a high significance level for the employment of affective strategies regarding the gender variable. As for good and poor proficiency learners, it has been shown that cognitive and compensation strategies have high employment frequency among both groups. However, the statistical analysis did not show that language proficiency significantly influences the employment of LLS. The results of the study have implications for modifying second-language pedagogy. It emphasises the need to enhance language learners' knowledge of the methods, so they are encouraged to employ more appropriate LLS at different stages of learning their second language. Aside from that, it raises awareness among language teachers on the importance of learning methods for language learners, as well as the impact of elements such as gender and degree of competence in the learner's choice of LLS as well as individual disparities among language learners in a learner-centered classroom.